SELF- DIRECTED LEARNING - Hafizullah, Mohammad; Aman, Wahaj (Annals of Allied Health Sciences, 2015)
“Half of what you will learn in medical school will be shown to be either wrong or out of date within 5 years of graduation; the trouble is that nobody can tell you which half, so the important to learn is how to learn on your own.” David l Sacket Medical science continues to grow at dizzy spells and it is our earnest duty as Allied Health Professionals to our patients, their families and colleagues to continue to learn, imbibe, question and reflect. It is our professional responsibility to become self-directed learners from the beginning and keep on refining it during our professional career. The transition from our graduate schools where the curriculum is well circumscribed to professional life where we have to define our goals and achieve them is like to be thrown in deep sea of wilderness and uncertainty. As a professional one is humbled to recognize that one understands only a miniscule part of what is known with painful realization of half of it being wrong or out of date in a few years.